Contiguous Osteomyelitis of Distal Extremities in Children. (February 2021) - Nandavar, Akshay Vivek; Toledano, Talya; Marino, Catalina; Khanna, Shefali; Sitnitskaya, Yekaterina
Objective . To evaluate the burden of Contiguous Osteomyelitis (COM) in pediatric patients with cellulitis/abscess of hands/feet. Methods . Children aged 0-18 years, treated from 2009 to 2019 for cellulitis/abscess of hands/feet, who either had Magnetic Resonance Imaging at presentation, or Roentgenogram >10 days after symptom-onset, were included. Two-tailed T-test was used to compare patients with and without COM. P -value < .05 deemed statistically significant. Results . Twenty of forty-one patients with abscess/cellulitis of distal extremities were diagnosed with COM. Between groups, no differences identified in trauma-to-presentation time, antibiotic treatment for >48 hours before admission, abscess versus cellulitis, location of infection, presence of fever, or signs of infection. Conclusion . In our cohort, clinical presentation did not differentiate COM. Imaging helped diagnose patients with COM, who would otherwise receive a shorter antibiotic course. Hands/feet imaging in pediatric patients hospitalized with cellulitis/abscess should be considered to identify COM and customize treatment. Further research is warranted.